Interest Rate Modelling and Forecasting Macro-Finance Approach - Kučera, Adam (2014)
The thesis compares various approaches to the term structure of interest rates modelling. Several models are built, following two general frameworks: a dynamic Nelson-Siegel approach and an affine class of models. Based on an evaluation of dynamic properties of the estimated models, particularly in terms of impulse-responses and a forecasting performance, effects of an explicit inclusion of macroeconomic variables into the models are tested. The thesis shows, that the benefit of such macro-finance extension of the models is varying in time, and also differs for both approaches. However, it is shown that the models can be considered as complementary, as the particular approaches are differently useful under various macroeconomic conditions and financial markets situations. Moreover, unusually long maturities are included into the term structure of interest rates, and some of the models are shown to be able to forecast these maturities as well, particularly in certain periods of time.